The Development of Photocatalytic Systems Entitled Titanium Dioxide Nanoparticles Attached to Polypropylene Fibrous Carrier for Freshwater Disinfection; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Lysak I. A. Ilya Aleksandrovich; Lysak G. V. Galina; Malinovskaya T. D. Tatyana; Ruhov A. S. Anatoly (2014, 2014)
Title screen